Population-based HIV prevalence, stigma and HIV risk among trans women in Nepal - Erin C. Wilson; Manisha Dhakal; Sanjay Sharma; Anuj Rai; Rajesh Lama; Sirish Chettri; Caitlin M. Turner; Hui Xie; Sean Arayasirikul; Jess Lin; Swagata Banik (BMC Infectious Diseases, 2021)
Abstract Background Transgender women (trans women) in Nepal are underserved in the HIV response. Data are needed to determine the HIV prevalence disaggregated from other key populations and to identify the particular risks faced by this community. Trans women are marginalized around the world and research is also needed to determine the impact of stigma on HIV risk to inform trans-specific interventions. Methods In 2019, we conducted the first population-based HIV behavioral surveillance study of trans women disaggregated from other key populations using respondent driven sampling (RDS). We estimated the HIV prevalence for trans women, and bivariate and multivariate Poisson binomial regression models were constructed to examine the relationship between HIV risk and stigma. Results Trans women participants (N = 200) had a mean age of 33 years old (SD = 10.96). We found a weighted HIV prevalence of 11.3% (95% CI 6·82% - 18·13). We found that depression and anxiety (aPR 0.81; 95% CI 0.67–0.97; p = 0·02) and current engagement in sex work (aPR 1.31; 95% CI 1.01–1.71; p = 0·046) were significantly associated with greater prevalence of condomless receptive anal intercourse. We found that experienced stigma of ever being verbally abused due to gender identity was significantly associated with lower prevalence of depression and anxiety (aPR 0.42; 95% CI 0.20–0.87; p = 0·002). Feeling unaccepted in Nepali society and believing people thought they were a criminal because of their trans identity was significantly associated greater prevalence of current sex work (aPR 1.36; 95% CI 1.03–1.78; p = 0·03; aPR 1.45; 95% CI 1.03–2.07; p = 0.04). Every measure of experienced stigma assessed was significantly associated with greater prevalence of current engagement in sex work. Conclusions Trans women are highly stigmatized in Nepal, leading to individual and systems factors that impact their risk for HIV. Interventions are needed that support the economic and mental wellbeing of trans women to prevent their heighted risk of HIV from stigma.